The role of Islamic studies in muslim civilization in the globalized world: Malaysian experience - Kayadibi, Saim; Buang, Ahmad Hidayat (Jabatan Kemajuan Islam Malaysia, 2011)
There has been a notably high enhancement in the mobility of researchers, institutions and programs in the global arena. With the result of globalization, attention of the intellectuals to Islamic studies and its civilization (Islam Hadhari) recently are being highly increased. Western as well as Eastern countries especially Malaysia aspires to play a central role for the world’s Islamic Higher Education Institutions. In achieving that essential goal, many institutions in Malaysia have introduced teaching of Islamic studies in English and Arabic beside Malay language. According to these changes the institutions have employed erudite scholars from different part of the world. This internalization process made the universities more popular among the intellectuals. This paper attempts to highlight the role played by Malaysia in Islamic Studies to reawaken process of Muslim Civilization on Higher Education with its special attention on globalization through the understanding of it with the technological components which withdraw physical and spiritual boundaries in the globalized world.